Characteristics of Tonsillitis in Children at Massenrempulu Enrekang Regional Hospital During The Period 2017-2022 - Far, TM, Duhri; Darussalam, Andi Husni Esa; Ikram, Dzul; Sanna, Andri Tenri; Jafar, Muhammad Alfian (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Tonsillitis, an inflammation of the tonsils due to viral or bacterial infection, manifests with symptoms such as sore throat, tonsil swelling, difficulty swallowing, and fever. While the World Health Organization (WHO) lacks specific global tonsillitis incidence data, Indonesian Ministry of Health's 2018 statistics rank tonsillitis as the 10th most common ailment among 5-9-year-olds. Objective to characterize tonsillitis among children at Massenrempulu Enrekang Regional General Hospital during 2017-2022. The method used is descriptive research with a univariate design. The total sample size is 93, using total sampling technique, and analyzed with a univariate design. The results obtained showed that the age characteristics were as follows: children aged 6-11 years constitute 41 patients (44.1%), early adolescents aged 12-16 years constitute 31 patients (33.3%), toddlers aged 0-5 years constitute 14 patients (15.1%), and late adolescents aged 17-18 years constitute 7 patients (7.5%). The distribution of gender indicates that female patients are 52 (55.9%), while male patients are 41 (44.1%). Parental education level shows that moderate education level is represented by 52 patients (55.9%), followed by high education level by 37 patients (39.8%), and low education level by 4 patients (4.3%). A history of upper respiratory tract infections was found in 85 patients (91.4%), while only 8 patients (8.6%) had no history of upper respiratory tract infections. Allergy history was present in 68 patients (73.1%), while 25 patients (26.9%) had no history of allergies.